Uma análise semiótica do Chanel Nº5 : do objeto embalagem ao discurso institucional - Malta, Fabrício Coelho (2014)
This research aims to examine, based on the theoretical framework of French semiotics, the primary and secondary packaging of the perfume Chanel No. 5 and its speeches about the product at the institutional site of the brand in order to identify, describe and analyze the values of the brand.The constitution of the corpus was made by reason of this intriguing fragrance to be one of the most seductive perfume, perhaps the best known and best selling in the world.Thus, we intend to prove, as the figures related to the refinement, luxury, seduction and innovation can be seen in packaging, reflecting the brand.Thus, the corpus will consist of the packaging and its verbal discourse, more specifically, the institutional video, "No.5 - Inside Chanel", bounded to the passages that deal with values that Chanel No. 5 builds. We intend, from a theoretical and analytical approach to the verbal text and syncretic text, apply systematic methodology by Greimas in his sense of the generative process, more specifically, the level of discourse that includes the level of discursive structures, to analyze the thematization and sense figuratively.The bottle design inspired by the Art Deco style, brings a solemn look, ultra simple and futuristic. The closure highlights a large faceted shape, like a diamond.It was found that the packaging has a speech and language itself, which adds value to the brand, there is a great similarity between the packaging and Chanel style, related by the opposition between the "black and white" and a relationship between freedom in the brand, which transfers to the packaging, from the object to its "fitness", an artifact of desire.Stylist, Chanel takes the thematic role of perfumer creating a new fragrance, coming to rise by recognizing his work. By means of figures and themes analyzed and expressed in the packaging of the perfume, there was the bottle and the box Chanel No. 5 as a strong marketing tool, able to convey the brand values to its intended audience. Keywords: packaging, semiotics, Chanel, brand.